EDUKASI URGENSI PENDIDIKAN UNTUK MENINGKATKAN MOTIVASI SEKOLAH SISWA - Rusydi, Lina Najwatur; Maulida, Wildatul; Arifin, Ghaniyah Geulis; Sholihin, Imam Ahmad; Wahyudi, Imam; Sari, Dewi Puspita (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2024)
The School Enrollment Rate (APS) in West Java province will increase in 2023 at the elementary school (SD), junior high school (SMP) and senior high school (SMA) levels. However, at the tertiary level it is still very low, namely 24.72% (BPS, 2023). Puraseda, as one of the villages in Bogor Regency, West Java Province, is also experiencing similar problems. School participation rates still need to be improved. This PKM activity aims to increase students' school motivation in order to increase school participation rates. The activity was carried out on September 7 2024 at Al-Barokah Middle School, Situhiyang Village, Puraseda Village, Leuwiliang District, Bogor Regency. The method used is education or counseling. Based on the results of PKM implementation, it was found that there was an increase in students' encouragement to continue their studies to a higher level